2020
DOI: 10.1186/s13046-020-01802-9
|View full text |Cite
|
Sign up to set email alerts
|

MIEF2 over-expression promotes tumor growth and metastasis through reprogramming of glucose metabolism in ovarian cancer

Abstract: Background Increasing evidence has revealed the close link between mitochondrial dynamic dysfunction and cancer. MIEF2 (mitochondrial elongation factor 2) is mitochondrial outer membrane protein that functions in the regulation of mitochondrial fission. However, the expression, clinical significance and biological functions of MIEF2 are still largely unclear in human cancers, especially in ovarian cancer (OC). Methods The expression and clinical si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Fragmentation of mitochondria is widely thought to promote tumor progression ( Trotta and Chipuk, 2017 ). Indeed, fission promoting proteins—including DRP1 ( Zhao et al, 2013 ), MFF ( Seo et al, 2019 ), FIS1 ( Karimi et al, 2021 ; Soares et al, 2019 ), and MiD49 ( Zhao et al, 2020 )—are often found to have increased expression in cancer compared to normal adjacent tissues ( Table 2 ). In an elegant study, one group observed how changes in DRP1 and MFN1 expression drives invasive and migratory phenotypes ( Zhao et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fragmentation of mitochondria is widely thought to promote tumor progression ( Trotta and Chipuk, 2017 ). Indeed, fission promoting proteins—including DRP1 ( Zhao et al, 2013 ), MFF ( Seo et al, 2019 ), FIS1 ( Karimi et al, 2021 ; Soares et al, 2019 ), and MiD49 ( Zhao et al, 2020 )—are often found to have increased expression in cancer compared to normal adjacent tissues ( Table 2 ). In an elegant study, one group observed how changes in DRP1 and MFN1 expression drives invasive and migratory phenotypes ( Zhao et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is generally accepted that mitochondrial fission is seen as promoting tumor growth and metastasis, the role of fission promoting receptor MiD49 (also known as MIEF2) in metastasis remains controversial. In ovarian cancer MiD49 mRNA and protein expression was increased in tumorigenic tissue in comparison to peritumor samples, and higher MiD49 expression correlated with worse overall and progression-free survival ( Zhao et al, 2020 ) ( Table 2 ). Indeed, ablation of MiD49 with siRNA increased mitochondrial length while reducing ovarian cancer cell growth, migration, invasion, tumor growth in and lung metastasis in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-16-5p and 15b-5p coregulate ALDH1A3, which can inhibit the ubiquitination of PKM2 and regulate glycolysis to exert anticancer effects (Huang X. et al, 2021). In ovarian cancer, miR-424-5p inhibits mitochondrial elongation factor 2 (MIEF2), which regulates mitochondrial fission, inhibits glucose metabolism from oxidative phosphorylation to glycolysis, and inhibits tumor growth (Zhao et al, 2020). LIX1-like protein (LIX1L) promotes miR-21-3p, inhibits FBP1, reduces lactic acid production, and affects sugar metabolism to inhibit tumor growth (Zou et al, 2021) (Figure 1).…”
Section: Non-coding Ribonucleic Acidsmentioning
confidence: 99%
“…According to a previous study, miR-424-5p modulates glucose metabolism during tumor growth and metastasis [ 218 ]. However, recent studies also showed that it affects lipid metabolism in cancer cells.…”
Section: Noncoding Rnas Regulate Both Tumor Metabolism and The Immune Microenvironmentmentioning
confidence: 99%